Evaluation of the extraction of antioxidant compounds from buriti pulp (Mauritia flexuosa L.) by response surface methodology - Gabriela Mota Nogueira; Flávia Aparecida Reitz Cardoso; Márcia Regina Ferreira Geraldo Perdoncini; Marcos Vieira da Silva; Eliane Sloboda Rigobello (Heliyon)
Buriti is a fruit rich in antioxidant compounds, and hydroalcoholic extracts were produced from its pulp to investigate the extraction conditions that result in the highest concentrations of bioactive compounds and maximum antioxidant capacity. The results showed considerable variation in the bioactive compound contents in the pulp: total phenolics (104.64–270.61 mg GAE 100 g-1), total flavonoids (17.74–60.46 mg EC 100 g−1), and total carotenoids (1.30–3.92 mg kg−1). The antioxidant capacity of the extracts, evaluated by DPPH, ABTS, and FRAP methods, ranged from 1.23 to 3.47 μmol ET g−1, 6.34–15.86 μmol ET g−1, and 4.74–11.95 μmol ET g−1, respectively, highlighting the broad diversity of antioxidant activities present in the extracts. Data modeling generated statistically significant mathematical models and contour graphs, which allowed the identification of the optimal extraction conditions for the compounds. Total carotenoids were most effectively extracted with 20 % buriti pulp, intermediate ethanol concentrations, and temperatures around 70 °C. All other bioactive compounds were more efficiently extracted with 5 % buriti pulp, intermediate ethanol concentrations, and temperatures close to 30 °C. The results confirmed the efficiency of the extractions and highlighted the excellent antioxidant potential of buriti pulp. Additionally, the analysis of the optimal regions for extracting antioxidant compounds from the pulp can be applied in future studies to optimize the extraction process, providing a solid foundation for using this fruit in industrial processes, such as the production of functional ingredients.